Challenges and Needs of Chinese and Korean American Breast Cancer Survivors: In-Depth Interviews - Lee, Sunmin; Chen, Lu; Ma, Grace X.; Fang, Carolyn Y.; Oh, Youngsuk; Scully, Lynn (North American Journal of Medicine and Science, 2013)
Breast cancer incidence and the number of breast cancer survivors have been rapidly increasing among Chinese and Korean women in the United States. However, few data are available regarding quality of life in Asian American breast cancer survivors. This qualitative study aims to describe Asian American women’s perceptions of quality of life and their breast cancer experiences. In-depth interviews with four Chinese and five Korean American breast cancer survivors and three oncologists were conducted in Chinese, Korean, or English. Interviews were recorded and transcripts were translated into English. Qualitative analyses were performed by two independent coders and then discussed and agreed upon by the research team. The respondents reported that the breast cancer experience had affected various domains of quality of life, but women reported having limited resources with which to cope effectively. Depression, anxiety, and stress were commonly reported, but women rarely discussed these issues with family and friends or sought professional help. As immigrants, women’s loneliness and a lack of social support and culturally relevant resources seemed to be major barriers to maintaining good quality of life. Women also expressed interest in learning more about alternative therapies and relaxation skills. These findings can be used to help inform the development of a culturally appropriate intervention for Asian American breast cancer survivors. Future programs may provide information in women’s native languages to teach skills to cope with stress and anxiety, increase women’s self-efficacy within the context of their cultural background, and enhance social support among women from the same ethnic group.